Congenital diaphragmatic hernia increases the sensitivity of pulmonary arteries to nitric oxide. (May 2023) - Bressan, Alecsander F.; Maia, Victoria Oliveira; de Souza Rodrigues, Beatriz; Bertozi, Giuliana; Batah, Sabrina S.; Fabro, Alexandre T.; Pelizzo, Glória; Pierucci, Ugo Maria; Tostes, Rita C.; Sbragia, Lourenço; Carneiro, Fernando S.
Abstract: Left congenital diaphragmatic hernia (CDH) can lead to pulmonary arteries abnormalities in the contralateral and ipsilateral sides of the diaphragm. Nitric oxide (NO) is the main therapy used to attenuate the vascular effects of CDH, but it is not always effective. We hypothesized that the left and right pulmonary arteries do not respond similarly to NO donors during CDH. Therefore, vasorelaxant responses of the left and right pulmonary arteries to sodium nitroprusside (SNP, a NO donor) were determined in a rabbit experimental model of left CDH. CDH was surgically induced in the fetuses of rabbits on the 25th day of pregnancy. On the 30th day of pregnancy, a midline laparotomy was performed to access the fetuses. The fetuses' left and right pulmonary arteries were isolated and mounted in myograph chambers. Vasodilation was evaluated by cumulative concentration-effect curves to SNP. Protein expression of guanylate cyclase isoforms (GCα, GCβ) and the α isoform of cGMP-dependent protein kinase 1 (PKG1α), and the concentration of NO and cGMP were determined in the pulmonary arteries. The left and right pulmonary arteries of newborns with CDH exhibited increased vasorelaxant responses to SNP (i.e. the potency of SNP was increased) compared to the control group. GCα, GCβ, and PKG1α expression were decreased, while NO and cGMP concentrations were increased in the pulmonary arteries of newborns with CDH compared to the control group. The increased cGMP mobilization may be responsible for the increased vasorelaxant responses to the SNP in the pulmonary arteries during left CDH. Graphical Abstract: ga1